2019
DOI: 10.1111/cdoe.12465
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and dental caries experience in Nepalese schoolchildren

Abstract: Objectives:The aim was to investigate the severity of untreated dental caries among Nepalese schoolchildren and its association with their body mass index (BMI) using IOTF, WHO and Nepalese growth reference systems.Methods: This school-based clinical cross-sectional study was conducted with three WHO index age groups (5-to 6-, 12-and 15-year-olds) in 18 out of 75 districts of Nepal, selected using stratified random sampling. A total of 1135 schoolchildren were included in the study. A validated structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Across both age groups, severe caries by pufa+PUFA-an indication of deep dental infection, cavitation, and likelihood of dental pain-was associated with lower WAZ and BAZ, suggesting a risk for acute malnutrition, and in older children, severe caries by SiC was associated with lower HAZ, suggesting a risk for chronic malnutrition. This study adds to the growing literature from developing countries, demonstrating that severe dental caries may exacerbate the risk for childhood malnutrition, especially in early childhood [29,32,33,36]. The pathophysiologic mechanisms by which severe caries may contribute to malnutrition include chronic infection/inflammation and dental pain suppressing children's appetite and growth, loss of tooth structure inhibiting children's ability to chew nutritious foods, and increasing use of non-nutritious sweets to pacify children's chronic pain [32].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Across both age groups, severe caries by pufa+PUFA-an indication of deep dental infection, cavitation, and likelihood of dental pain-was associated with lower WAZ and BAZ, suggesting a risk for acute malnutrition, and in older children, severe caries by SiC was associated with lower HAZ, suggesting a risk for chronic malnutrition. This study adds to the growing literature from developing countries, demonstrating that severe dental caries may exacerbate the risk for childhood malnutrition, especially in early childhood [29,32,33,36]. The pathophysiologic mechanisms by which severe caries may contribute to malnutrition include chronic infection/inflammation and dental pain suppressing children's appetite and growth, loss of tooth structure inhibiting children's ability to chew nutritious foods, and increasing use of non-nutritious sweets to pacify children's chronic pain [32].…”
Section: Discussionmentioning
confidence: 84%
“…There have been mixed findings on the association between severe caries and nutritional status. Studies have demonstrated an association between severe caries and malnutrition in some low-income contexts, with caries contributing to mouth pain and chronic inflammation which disrupt normal eating, sleep, and growth [29][30][31][32][33]; associations with obesity in high-income contexts due to shared dietary risk factors [34,35]; and no associations in other studies [36]. There is limited research on these relationships in Nepali populations.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hooley et al [ 13 ], both high and low BMI show association with caries. The association is different depending on the country’s developmental stage and socioeconomic situation [ 13 , 14 ]. Chen et al [ 35 ] in their systematic review found that obese children from high-income countries were more likely to have a higher caries prevalence than from low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Caries and obesity are both multifactorial diseases sharing similar risk factors such as a harmful diet, socioeconomic conditions [ 11 ] and lifestyle [ 12 ]. Literature on the association between overweight and caries is contradictory; both high and low BMI showing an association with decaying teeth in children [ 13 , 14 ]. The association depends on the country’s stage of development as well as on socioeconomics [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intake of starch and its association with the risk of occurrence of dental caries was not found as a result of conducting a systemic review but it was recommended that higher intake of starch which has ability to quickly digestible may elevate the caries risk. 6 Sweet choices as well as consumption of sweet in the form of coffee and tea are associated with the experience of dental caries as reported in many studies 7,8,9,10,11,12 .…”
Section: Introductionmentioning
confidence: 96%